KARAKTERISTIK UMUR PRODUK PADA MODEL WEIBULL - Sudarno, Sudarno (MEDIA STATISTIKA, 2009)
Long life of product can reflect its quality. Generally, good products have long life. There are functions that relationship with life as reliability function, hazard rate function, mean time to failure, and mean residual life. In this writing those functions be used to product which has the failure time of a component is distributed Weibull. The reliability function is exponential function. For value θ is constant, the reliability value is decrease function, if γ is greather with respect to time. Meanwhile hazard rate function could be monotone increase function, constant function, monotone decrease function, if doing by simulation with shape parameter by one. Really, the mean time to failure product hang on Weibull distribution parameters. But the mean residual life is reciprocal with respect to its reliability.   Keywords:      Weibull Model, Reliability and Hazard Rate Functions, Mean Time to Failure, Mean Residual Life.